Pengaruh Kewajiban Kepemilikan NPWP, Pemahaman Perpajakan, Kesadaran Wajib Pajak Pribadi Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Kasus Pada Wajib Pajak Orang Pribadi di KPP Pratama Malang Utara) - Khotifah Ayu Febriyanti; Afifudin Afifudin; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This research answers the problem of factors that influence taxpayer compliance consisting of the variable obligation to own TIN, understanding of taxation, and awareness of taxpayers for WPOP in the KPP Pratama area of North Malang. This research is quantitative research using primary data. Primary data was obtained from a questionnaire that was measured using a Likert scale. Ninety-five respondents were obtained based on the slovin formula method. Data analysis using multiple linear regression models. This study shows that the obligation to own a TIN does not affect individual taxpayer compliance. In contrast, understanding of taxation and awareness of personal taxpayers has a positive and significant effect on individual taxpayer compliance.Keywords: NPWP, Understanding of taxation, awareness, compliance